The Mediating Role of Price in Service Quality for MSME Product Purchases - Indrawati, Mei; ., Chamariyah; Halima, Nur; ., Irawan; ., Rusdiyanto (Journal of Ecohumanism, 2024)
This research examines how price and service quality affect MSME product purchases and how service quality influences price in the MSME product purchasing process in Indonesia. For this study, 96 MSME clients in Indonesia chosen by simple random sampling were given online questionnaires as part of a quantitative research project that used an online survey methodology with Google Forms. A five-point Likert scale was used to create the online survey, which was shared on social media. Using data processing tools and SmartPLS version 3.0 software, data analysis is done using Structural Equation Modeling of Partial Least Squares (SEM-PLS).The study’s conclusions show that service quality has a substantial and positive influence and can act as a mediating factor for the indirect effect of pricing on decisions to buy (p<0.05). In addition, pricing significantly influences decisions to buy (p<0.05). R squared indicates a moderate influence of price and service quality together on purchasing decisions (0.488). However, the impact of the f square effect size (f square = 0.023) in mediating the role of service quality is minimal. All things considered, the PLS model has a reasonable robustness check (sample linearity and heterogeneity are met), a high goodness of fit index (0.548 > 0.36), and an acceptable SRMR (0.087 < 0.10).